Electrical resistivity structure in the Tocomar geothermal system obtained from 3-D inversion of audio-magnetotelluric data (Central Puna, NW Argentina). (September 2022) - Ahumada, M.F.; Guevara, L.; Favetto, A.; Filipovich, R.; Chiodi, A.; Viramonte, J.G.; Giordano, G.
Highlights: The Central Andes are the largest undeveloped geothermal region in the world. Geophysic method that use the natural variations of the electric and magnetic fields. 3-D inversion is a promising technique to model and image geothermal reservoirs. Low-resistivity layer is linked with the clay cap at the geothermal reservoir. Conceptual model for high-temperature volcanic geothermal systems. Abstract: The Tocomar Geothermal System is located in the Puna Plateau (NW Argentina), within the Central Puna Energy Hub, and is considered one of the most promising places to harness potential alternative of power and heat sources in the Central Andean Volcanic Zone (16-28 °S). It is related to the Calama-Olacapato-Toro lineament and to the Quaternary Tocomar volcanic centre. Moreover, it is surrounded by active and fossil geothermal manifestations, like hot-springs, travertines and siliceous sinter deposits. Despite some geological studies in the area, no geophysical investigations have targeted the geothermal fields along the Central Puna. In this work we present a 3-D inversion of audio-magnetotelluric data around the Tocomar Geothermal System. These data was obtained in the frequency range of 1000-0.1 Hz to map the main elements of the geothermal system (clay cap and potential reservoir) at depths of approximately 1000 m. To achieve this goal, previous geoelectrical studies, the local geology and the trend of the main structures were also considered. For the 3-D inversion process the ModEM code was used. The model shows a low-resistivity layer (less than 10 Ωm) at least 300 m thick, at a depth of about 200–500 m, aligned with both the strike of the Calama-Olacapato-Toro lineament and the local superficial geothermal manifestations (hot-springs and hydrothermally altered rocks). This low-resistivity layer is linked with the clay cap at the shallow depth of the geothermal reservoir. At depths greater than 800 m, a gradual increase in resistivity is observed related to a potential reservoir within the fractured Ordovician basement. The final 3-D resistivity model highly correlates with the conceptual models of high-temperature volcanic geothermal systems.